Musculoskeletal Injuries and Ophthalmologists: Prevention Requires a System-Level Approach: A Roundtable Discussion - Mather, Rookaya; Masket, Samuel; Zavitz, Terry; Dhaliwal, Deepinder (Canadian Eye Care Today, 2024)
Musculoskeletal injuries make up about 15% of physicians’ insurance claims. These injuries lead to patient care disruptions, cancelled surgeries, significant disability, and early retirement. Dr. Rookaya Mather sat down with three fellow advocates for physician wellness and WMSD prevention, including two fellow ophthalmologists and a disability insurance expert. They discussed the factors that contribute to injury – from the culture of medicine to suboptimal ergonomic design of examination and surgical equipment – and the role that insurance companies, practising ophthalmologists, academic institutions, and manufacturers can play in preventing injury.